Influence of blade geometry on secondary flow development in a transonic centrifugal compressor. (27th September 2018) - Mosdzien, Moritz; Enneking, Martin; Hehn, Alexander; Grates, Daniel; Jeschke, Peter
Abstract : Due to the increasing demand for higher efficiencies of centrifugal compressors, numerical optimization methods are becoming more and more relevant in the design process. To identify the beneficial features of a numerical optimized compressor design, this paper analyses the influence of arbitrary blade surfaces on the loss generation in a transonic centrifugal compressor. The paper therefore focuses on an analysis of the secondary flow development within the impeller blade passages. To do this, steady simulations were performed on both a baseline and an optimized blade design. Two distinct design features of the optimized compressor stage were identified, which lead to a more homogenous impeller exit flow and thus to an increase in total-to-static efficiency of 1.76% points: the positive lean in the near-tip region and the positive blade curvature in the rear part of the optimized impeller. Furthermore, through extensive experimental investigations conducted on a large scale test rig it has been possible to prove the particular impeller outflow characteristics of the baseline compressor stage.